Wheat and Rice Growth Stages and Fertilization Regimes Alter Soil Bacterial Community Structure, But Not Diversity - Wang, Jichen; Xue, Chao; Song, Yang; Wang, Lei; Huang, Qiwei; Shen, Qirong (Frontiers in Microbiology, 2016)
Maintaining soil fertility and the microbial communities that determine fertility is critical to sustainable agricultural strategies, and the use of different organic fertilizer regimes represents an important practice in attempts to preserve soil quality. However, little is known about the dynamic response of bacterial communities to fertilization regimes across crop growth stages. In this study, we examined microbial community structure and diversity across eight representative growth stages of wheat-rice rotation under four different fertilization treatments: no nitrogen fertilizer (NNF), chemical fertilizer (CF), organic-inorganic mixed fertilizer (OIMF) and organic fertilizer (OF). Quantitative PCR (QPCR) and high-throughput sequencing of bacterial 16S rRNA gene fragments revealed that growth stage as the best predictor of bacterial community abundance and structure. Additionally, bacterial community compositions differed between wheat and rice rotations. Relative to soils under wheat rotation, soils under rice rotation contained higher relative abundances (RA) of anaerobic and mesophilic microbes and lower RA of aerophilic microbes. With respect to fertilization regime, NNF plots had a higher abundance of nitrogen–fixing Cyanobacteria. OIMF had a lower abundance of ammonia-oxidizing Thaumarchaeota compared with CF. Application of chemical fertilizers (CF and OIMF treatments) significantly increased the abundance of some generally oligotrophic bacteria such those belonging to the Acidobacteria, while more copiotrophic of the phylum Proteobacteria increased with organic fertilizer application. A high correlation coefficient was found when comparing RA of Acidobacteria based upon QPCR versus sequence analysis, yet poor correlations were found for the Alpha- and Beta- Proteobacteria, highlighting the caution required when interpreting these molecular data. In total, crop, fertilization scheme and plant developmental stage all influenced soil microbial community structure, but not total levels of alpha diversity.